Prognostic value of Musashi 2 (MSI2) in cancer patients: A systematic review and meta-analysis - Jiang, Lin; Xue, Shanshan; Xu, Jie; Fu, Xiaoyang; Wei, Jing; Zhang, Chuanmeng (Frontiers in Oncology, 2022)
Musashi 2 (MSI2) is an RNA-binding protein that regulates mRNA translation of numerous intracellular targets and plays an important role in the development of cancer. However, the prognostic value of MSI2 in various cancers remains controversial. Herein, we conducted this meta-analysis including 21 studies with 2640 patients searched from PubMed, Web of Science, EMBASE, Chinese National Knowledge Infrastructure databases, and WanFang databases to accurately assess the prognostic significance of MSI2 in various cancers. Our results indicated that high MSI2 expression was significantly related to poor overall survival (HR = 1.84, 95% CI: 1.66-2.05, P < 0.001) and disease-free survival (HR = 1.73, 95% CI: 1.35-2.22, P < 0.001). In addition, MSI2 positive expression was associated with certain phenotypes of tumor aggressiveness, such as clinical stage, depth of invasion, lymph node metastasis, liver metastasis and tumor size. In conclusion, elevated MSI2 expression is closely correlated with poor prognosis in various cancers, and may serve as a potential molecular target for cancer patients.